Inhibitory effect of propolis and bee venom on the mutagenicity of some direct-and indirect-acting mutagens - Varanda, Eliana A. [UNESP]; Monti, Rubens; Tavares, Denise C. (My University, 1999)
The antimutagenic effect of ethanolic extract of propolis (EEP) and honeybee (Apis mellifera) venom, both collected in the State of Sao Paulo, Brazil, was assessed by the Salmonella/microsome assay upon direct- and indirect-acting mutagens. EEP had inhibitory effect (in an ascending order) on the mutagenicity power of daunomycin (TA102), benzo(a)pyrene (TA100), and aflatoxin B1(TA98) and the venom acted against the mutagenicity of 4-nitro- o-phenylenediamine (TA98) and daunomycin (TA102).
Keywords: Antimutagenicity; Bee venom; Direct and indirect mutagens; Propolis